2002
DOI: 10.1002/dmrr.322
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of endothelin‐1 and sodium hydrogen exchanger‐1 in the diabetic myocardium

Abstract: These results indicate an important contribution of both ET-1 and NHE-1 in the pathogenesis of diabetic cardiomyopathy. These data suggest that NHE-1 may act as a downstream mediator in the production of ET-induced functional and structural changes in the myocardium in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
53
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 58 publications
3
53
1
1
Order By: Relevance
“…The same study also demonstrated the alteration of several microRNAs (miRNAs) in EndMT of nondiabetic etiology (5). We previously demonstrated EndMT in the retina of diabetic animals (8) as well as a pathogenetic role of endothelin 1 (ET-1) in diabetic cardiomyopathy (3,4). Of note, ET-1 has been demonstrated to be of significance in EndMT in the diabetic heart (9).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The same study also demonstrated the alteration of several microRNAs (miRNAs) in EndMT of nondiabetic etiology (5). We previously demonstrated EndMT in the retina of diabetic animals (8) as well as a pathogenetic role of endothelin 1 (ET-1) in diabetic cardiomyopathy (3,4). Of note, ET-1 has been demonstrated to be of significance in EndMT in the diabetic heart (9).…”
mentioning
confidence: 88%
“…Endothelial cells (ECs) are initial targets of hyperglycemic damage and play a major role in the production of ECM proteins in all chronic diabetic complications. At the structural level in the heart, such changes are manifested as thickening of the capillary basement membrane, focal myocardial fibrosis, and so forth (3,4). A result of sustained injury in the fibrotic diseases is that ECs undergo a process of transdifferentiation (i.e., endothelial-to-mesenchymal transition [EndMT]) (5,6).…”
mentioning
confidence: 99%
“…Recently, the benefit of endothelin receptor antagonist in attenuating diabetes mellitus-induced myocardial dysfunction in experimental studies was reported. [12][13][14][15][16][17][18] Most of the aforementioned studies demonstrate attenuation of fibrosis, restoration of vascular hyperactivity, and improvement of cardiac function as the important features of ET-1 receptor blockade; however, such pharmacology-based studies are not able to identify the molecular mechanism linking ET-1 to diabetic cardiomyopathy.…”
Section: Clinical Perspective On P 2418mentioning
confidence: 99%
“…Recently, the benefit of endothelin receptor antagonist in attenuating diabetes mellitus-induced myocardial dysfunction in experimental studies was reported. [12][13][14][15][16][17][18] Most of the aforementioned studies demonstrate attenuation of fibrosis, restoration of vascular hyperactivity, and improvement of cardiac function as the important features of ET-1 receptor blockade; however, such pharmacology-based studies are not able to identify the molecular mechanism linking ET-1 to diabetic cardiomyopathy.Homozygous deletion of ET-1 in mice is a useful approach for investigating ET-1 signaling in embryonic development; however, early postnatal lethality caused by craniofacial abnormalities precludes the use of these mice in exploring the role of ET-1 in adult physiology. 19 Previously, using the Cre-loxP recombinase system, we generated mice with conditional knockout of ET-1 exclusively in endothelial cells (Y.Y.K.…”
mentioning
confidence: 99%
“…Diabetes-induced capillary basement membrane thickening, increased extracellular matrix (ECM) protein synthesis, and blood flow alterations in the heart are prevented by ET-receptor antagonism [8]. Studies have also suggested that the mechanism of ET-1 action in the heart may involve sodium hydrogen exchanger (NHE) [13]. Evidence from a variety of experimental models show that the cardiac effects of ET-1 may be mediated through the activation of Na + /H + exchange [14,15].…”
mentioning
confidence: 97%